METODE LEARNING BY DOING DALAM HADIS NABI - Arofatul Muawanah (Ta`Limuna: Jurnal Pendidikan Islam, 2023)
Abstract:In the current era, the development of learning methods is increasingly varied; by emphasizing two-way learning (student-centered-learning); so that what is targeted is mastery of the material and skills of students, including the learning by doing method which is considered appropriate to the needs of students in the 21st century. The hadith which is the reference for all actions also contains an explanation of the concept of learning by doing. Therefore, this study aims to find out how the concept of learning by doing actually works in the hadith of the Prophet. By using qualitative methods and content analysis approaches, this research concludes that the concept of learning by doing has actually been explained by the Prophet through a hadith that was recited by al Bukhari which was narrated from Anas bin Malik's best friend. The findings of this study are that the Prophet educated his companions not only focusing on mastering the material, but also trying to strengthen the skills and creativity of the companions to prepare them to deal with the problems that occurred around them